Development of Macromedia Flash-Based Basketball Teaching Materials for Students' Physical Education, Sports and Health 10th Grade Senior High School Methodist 8 Medan - Firman Benhard Silaen; Indra Kasih; Novita Sari Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to produce learning media for basic basketball techniques based on Macromedia Flash for X grade high school students that can be used by students as a learning resource independently. The type of research used is research and development (R&D), namely the development of learning materials based on Macromedia Flash. This learning media development model was developed based on the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the trial were students of class X SMA Methodist-8 Medan which consisted of small group trials of 15 students and large group trials of 30 students. The instrument used to collect data in this research and development is a questionnaire or questionnaire. The data analysis technique used descriptive statistical analysis. The results showed that the learning media for basic techniques of basketball based on Macromedia Flash for grade X SMA students were feasible to be used as a learning resource for students. This is indicated by several assessments that have been carried out by media experts, material experts and field trials. The final result of the assessment of the media expert shows that the basic basketball technique is declared "very good" with a percentage of 86% and the results of the assessment of the material expert show the category of "very good" with a percentage of 85%. The results of the small group trial got the "Good" category with a percentage of 90.76% and the results of the large group trial got the good category with a percentage of 95.38%.